(untitled) (BIRDEM Medical Journal, 2014)
Male subfertility is common, and it causes significant distress to couples. The most common cause of male subfertility is idiopathic failure of spermatogenesis, Compared to reproductive specialists, endocrinologists may see a population of men that have a higher prevalence of treatable causes of subfertility including sexual disorders, endocrinopathies, obesity, drugs, and ejaculatory dysfunction. Seminal fluid analysis is the most important diagnostic study, and at least 2 samples should be analyzed. All patients with sperm concentrations < 10 million/mL due to idiopathic spermatogenic defects should be referred for genetic counseling and karyotyping; most experts also recommend that these patients be tested for Y chromosomal microdeletions. For most men with low sperm concentrations due to gonadotropin deficiency, gonadotropin therapy effectively increases spermatogenesis. The endocrinologist must recognize when to use medical therapy to stimulate spermatogenesis and when to refer for consideration of assisted reproductive technology. Birdem Med J 2014; 4(2): 94-104